A method for imputing economic value to ecological goods and services provided by the Knysna River - Saunders, James Woodward (Rhodes University, Faculty of Commerce, Investec Business School, 2008)
The purpose of this thesis was to develop a method by which economic value can be imputed from an economic activity to a non-market ecological function or service which contributes to that economic activity. The Knysna River in South Africa was chosen as the ecological function which supported three economic activities from which value was to be imputed; these were the Knysna Municipal Water Supply, Fish Production in the Knysna Estuary and Production of Indigenous Forest within the Knysna Catchment. Three underlying assumptions and two functional operations were required in order to implement the suggested method. The underlying assumptions were: - The ecological and economic activities considered are within a single catchment. - The allocation of value imputed for a specific economic activity to the ecological function or service under consideration (in this case the Knysna River) is proportional to the total contribution of ecological functions or services contributed to the economic activity. - The valuation of the economic activity for the purposes of obtaining a price-quantity point on a demand function is to be full cost pricing with no producer surplus. The two functional requirements were: - Diagram or map the linkages between an economic activity and the supporting ecological functions. - Determine the consumer surplus related to an incremental change in quantity under a demand function where the original price and quantity are known. A value from each of the economic activities was imputed to the Knysna River. However, the method was not tested. Nonetheless applying the equations and collecting the required data allowed several methodological needs to be clearly pointed out. The most acute deficiency was difficulty in obtaining secondary data from governmental agencies, commercial representatives and existing published academic research to ensure a robust price. Also, scientific information was not sufficiently available for allocating ecological contributions to the economic activities. Even with the shortage of credible data the method appears to allow non-market ecological functions to be valued in context of an existing economic system.
Keywords: Ecology -- South Africa -- Knysna; Fishery management -- South Africa -- Knysna; Water-supply -- South Africa -- Knysna; Knysna Lagoon (South Africa); Knysna (South Africa) -- Economic conditions